SUPERVISION OF THE HEAD OF MADRASAH IN IMPROVING THE PROFESSIONALISM OF TEACHERS AT THE THAWALIB TANJUNG LIMAU ISLAMIC BOARDING SCHOOL - Ramadhani, Suci (PROGRES PENDIDIKAN, 2025)
The purpose of this study is to describe how the principal ofThis study is to describe how the principal of the school as a supervisor in improving and balancing the professionalism of teachers at the Thawalib Tanjung Limau Islamic Boarding School. as a supervisor in improving and balancing the professionalism of teachers at the Thawalib Tanjung Limau Islamic Boarding School. The methods used in conducting this study are qualitative descriptive methods based on observations of the principal and researchers. used to carry out this research is a qualitative descriptive method based on observations of the principal and researchers. research findings show that the role of the supervisor as a supervisor is actually carried out legally by carrying out various tasks, such as organizing academic supervisors, implementing academic supervision, and evaluating academic supervisors. the role of the supervisor as a supervisor is actually carried out legally such as by carrying out various tasks such as organizing academic advisors, implementing academic advisors, and evaluating academic advisors supervisors. Improving the supervisor's ability to supervise the ability by providing guidance to teachers in using learning media, providing opportunities for students to practice reading and writing, and so on. supervising students by providing guidance to teachers in using learning, allowing students to practice reading and reading and writing, and so on.